2012
DOI: 10.3122/jabfm.2012.03.100307
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities and Barriers to Colorectal Cancer Screening in Rural Areas

Abstract: Introduction: This study examined barriers to colorectal cancer (CRC) screening in people living in rural areas.Methods: We identified 2 rural counties with high rates of CRC and randomly contacted county residents by telephone using a published listing.Results: Six hundred thirty-five of the 1839 eligible respondents (34.5%) between the ages of 50 and 79 years living in McDuffie and Screven counties, Georgia, agreed to complete the survey. The mean age was 62.2 years (SD, ؎7.5 years); 72.4% were women, 79.4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
54
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 28 publications
(29 reference statements)
6
54
0
3
Order By: Relevance
“…Studies reported several types of patient fear: 1) fear of pain during colonoscopy; 2) fear of invasion during colonoscopy; 3) fear of bowel preparation; 4) fear of sedation or of hospital setting; and 5) fear of receiving a cancer diagnosis. 1822, 2425, 2728,3032 Fear of perceived “invasion” during colonoscopy was a common theme among African American males in particular. 1821,24,2728,30 Male respondents in focus groups and cognitive interviews described colonoscopy as “offensiveness,” “violating,” and “treading on my masculinity.” 18,24,27 Cancer-related fear stemmed from concerns about being diagnosed with cancer 19, 21, 25, 28,30 and of cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies reported several types of patient fear: 1) fear of pain during colonoscopy; 2) fear of invasion during colonoscopy; 3) fear of bowel preparation; 4) fear of sedation or of hospital setting; and 5) fear of receiving a cancer diagnosis. 1822, 2425, 2728,3032 Fear of perceived “invasion” during colonoscopy was a common theme among African American males in particular. 1821,24,2728,30 Male respondents in focus groups and cognitive interviews described colonoscopy as “offensiveness,” “violating,” and “treading on my masculinity.” 18,24,27 Cancer-related fear stemmed from concerns about being diagnosed with cancer 19, 21, 25, 28,30 and of cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…19, 2122, 26, 28,30,31,33 African Americans were often not aware of their increased risk of CRC. 21, 30, 33 For example, in one survey of 76 African American participants, only 16% believed that African Americans had a higher risk of CRC than Whites, and only 53% believed that CRC was preventable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations